2012
DOI: 10.1016/j.jcin.2012.02.010
|View full text |Cite
|
Sign up to set email alerts
|

Predictive Factors, Efficacy, and Safety of Balloon Post-Dilation After Transcatheter Aortic Valve Implantation With a Balloon-Expandable Valve

Abstract: BPD was needed in about one-fourth of the patients undergoing TAVI with a balloon-expandable valve and was successful in about one-half of them. A higher degree of valve calcification and transfemoral approach predicted the need for BPD. BPD was not associated with any deleterious effect on valve function at mid-term follow-up, but a higher rate of cerebrovascular events was observed in patients who had BPD.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
135
5
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 200 publications
(159 citation statements)
references
References 22 publications
(23 reference statements)
11
135
5
1
Order By: Relevance
“…PD has been performed due to frame under-expansion in most cases, and it was required in 22.7% of patients. This rate was quite similar to that reported in previous studies with a post-dilation rate of 30% to 38% after implantation of self-expanding prostheses and 28% to 41% for balloon-expandable valves [15,17,23,24,26]. PD might be associated with a higher rate of cardiovascular complications, conduction disturbances, annulus rupture, coronary obstruction, and cerebral embolism leading to stroke [1,4].…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…PD has been performed due to frame under-expansion in most cases, and it was required in 22.7% of patients. This rate was quite similar to that reported in previous studies with a post-dilation rate of 30% to 38% after implantation of self-expanding prostheses and 28% to 41% for balloon-expandable valves [15,17,23,24,26]. PD might be associated with a higher rate of cardiovascular complications, conduction disturbances, annulus rupture, coronary obstruction, and cerebral embolism leading to stroke [1,4].…”
Section: Discussionsupporting
confidence: 89%
“…Balloon post-dilatation (PD) can reduce PVL by achieving a better expansion of the prosthesis and optimal sealing of the paravalvular space. Valve-in-valve implantation is another option to overcome significant PVL, especially if the implantation position is more deep or more shallow than expected [17][18][19]. However, data on the impact of PD on long-term outcomes after TAVI are scarce.…”
Section: Introductionmentioning
confidence: 99%
“…14 Although the majority of post-TAVR PVL is mild (7.8-40.8%), moderate (5-37.9%) and severe (0.5-13.6%) PVL occur frequently. 1,2,6,8,10,11,13,[15][16][17][18][19][20][21][22][23][24][25][26] The largest meta-analysis of TAVR outcomes estimates the incidence of residual moderate or severe aortic regurgitation after TAVR to be 7.4%. 27 The UK TAVR registry suggests moderate-severe PVL occurred more commonly with CoreValve implants (17.3%, versus 9.6% with the Edwards implants).…”
Section: Definition and Incidencementioning
confidence: 99%
“…PAR is common in patients and has been reported to some degree in as much as 76% of cases. Severe PAR (grade 3 or 4) has been reported in approximately 17% of TAVI patients (Nombela-Franco et al 2012). Abdel-Wahab et al (2011) reported that if severe PAR does occur, the incidence of in-hospital mortality is increased from 6.7% to 16.5%.…”
Section: Introductionmentioning
confidence: 99%